Development of interactive learning media of automotive lighter vehicle maintenance machine in SMK N 1 Padang - Putra, Meiyaldi Eka; Maksum, Hasan (Universitas Negeri Padang, 2020)
Learning Media for Automotive Vehicle Engine Maintenance still uses a simple medium consisting of whiteboards and worksheets, which encourages less effective learning to develop more interactive media and supports students to more easily understand the basic concepts of Automotive Light Vehicle Engine Maintenance lessons. This development research aims to develop interactive learning media that is packaged interactively in the subject of Automotive Light Vehicle Engine Maintenance. This research method is R&D with One Group Pretest-Posttest design. The procedure of this research was carried out in the stages of defining, designing and developing. The subjects of this study were 28 students from SMK N 1 Padang in class XI OTO A. The data collected in this study consisted of primary data obtained directly from respondents in the format obtained. This research instrument consisted of a questionnaire of validity, practicality and effectiveness. The research data collected was analyzed using t test analysis. The results obtained from this research and development are as follows: (1) the validity of interactive learning media is stated to be very valid from didactic, construction and technical requirements with an average score of 94.16%. (2) The practicality of interactive learning media is stated to be very practical based on teacher responses with an average score of 95%, based on student responses also expressed very practical with an average score of 91.17%. (3) The effectiveness of interactive learning media can be seen from student learning outcomes before and after using the media. This is evidenced by the significant differences in the use of interactive learning media obtained from student learning outcomes. Improved student learning outcomes are changed by the students' completeness value of KKM with an average value of 86.61, which means students are complete in learning.